Sampling frequency of fetal heart rate impacts the ability to predict pH and BE at birth: a retrospective multi-cohort study - Li, Xuan; Xu, Yawen; Herry, Christophe; Durosier, L Daniel; Casati, Daniela; Stampalija, Tamara; Maisonneuve, Emeline; Seely, Andrew J E; Audibert, Francois; Alfirevic, Zarko; Ferrazzi, Enrico; Wang, Xiaogang; et al. (Physiological measurement, 2015)
Fetal heart rate (FHR) sampling rate used on the bedside is equal or less than 4 Hz. Current FHR analysis methods fail to detect incipient fetal acidemia. In a fetal sheep model of human labour we showed that FHR sampling rates near 1000 Hz are needed to detect fetal acidemia. Trans-abdominal fetal ECG (t-a fECG) sampling FHR at 900 Hz combined with a complex signals bioinformatics approach showed promise in a human cohort. Here we validate this finding in a retrospective human cohort study by comparing the performance of the same bioinformatics approach to predict pH and BE at birth in the cohorts with FHR sampled either at 4 Hz or at 900 Hz. The 4 Hz FHR recording data sets consisted of the open access intrapartum CTG data base with n = 552 subjects used to develop the predictive model and another cohort of prospectively recruited n = 11 labouring women to then validate it. 900 Hz FHR data set comprised two prospectively recruited t-a fECG cohorts of n = 60 and n = 23 subjects. Recruitment criteria were similar across the cohorts. We have determined the goodness of fit (R2) and root mean square error (RMSE) as the performance indicators of the model on each cohort. The clinical characteristics of all cohorts were similar (gestational age 280   ±   8 d; gender 50% male; birth body weight 3.5   ±   0.5 kg; pH and BE at birth 7.25   ±   0.1 and  −5.7   ±   3.4 mmol L  −  1, respectively; 1′ and 5′ Apgar scores at birth 8.5   ±   1.4 and 9.4   ±   0.6, respectively). The 4 Hz FHR cohort rendered-for pH and BE-R2 = 0.26 and 0.2 and RMSE = 0.087 and 3.44, respectively. This could not be confirmed in the validation cohort for neither pH nor BE prediction. The 900 Hz FHR cohort rendered-for pH and BE-R2 = 0.9 and 0.77 and RMSE = 0.03 and 1.70, respectively, and the pH prediction was validated. In our model, lower FHR sampling rate increased the predicted error range ~3-4 fold. We show that increasing FHR sampling rate to 900 Hz improves prediction of fetal pH and BE at birth. This should improve early identification of babies at risk of brain injury.